ECONOMIC DIRECTIONS OF STATE FINANCIAL POLICY MODERNIZATION FOR SUSTAINABLE DEVELOPMENT OF UKRAINE - Romanchukevych , V.V. (The actual problems of regional economy development, 2019)
The article is aimed at identifying the economic directions of the state financial policy modernization for sustainable development of Ukraine. Five basic dimensions of sustainable development formation are investigated: energy security, integration of the domestic energy market, economic union, a progressive policy for the use of globalization, justice and the fundamental rights of citizens. In addition, it was found that migration improves the process that promotes sustainable development. Migration policy must be built on solidarity and responsibility and will have the added benefit of making a valuable contribution to economic development and efficiency in the long term. Based on five main dimensions of research that stimulates economic development, the main directions for improving the state financial policy of sustainable development have been formed: improvement of the investment climate, formation of a single digital market, joining the structure of the European Energy Union. The author has formed the main economic direction indicators of the sustainable development financial policy: GDP per capita; extraction of energy raw materials; extraction of non-metallic and building materials; as well as ore; share of non-renewable energy in gross domestic energy consumption; contribution of electricity produced from renewable energy sources; production of electricity by sources and fuel; energy intensity of the economy; final consumption of fuel and energy in economic sectors, as well as electricity in economic sectors; production of radioactive waste; cargo productivity; productivity of passenger transportation; fare calculation per capita by public transport. It is established that the economic direction indicators of the sustainable development financial policy are aimed at improving the economic condition of th